DIGITAL EDUCATION TOOLS FOR INNOVATIVE TEACHERS AND STUDENTS IN THE FEDERAL REPUBLIC OF GERMANY - Suchkova, Svitlana; Suchkova, Olena (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
Modern realities affect the education sector. Global digitalization and the need for distance learning affect both technical aspects and teaching methods. The educational competencies of teachers and students, such as Learning, Finding, Thinking, Collaborating, Committing, Adapting, are influenced by technical factors of educational development and require a flexible approach to the implementation and introduction of the latest tools. The article discusses the possibilities of introducing digital education tools for innovative teachers and students in the Federal Republic of Germany using illustrative examples.